Topical Themes in Argumentation Theory
X, 346 p.
Keywords: Topical Themes in Argumentation Theory brings together twenty exploratory studies on important subjects of research in contemporary argumentation theory. The essays are based on papers that were presented at the 7th Conference of the International Society for the Study of Argumentation (ISSA) in Amsterdam in June 2010. They give an impression of the nature and the variety of the kind of research that has recently been carried out in the study of argumentation. The volume starts with three essays that provide stimulating theoretical perspectives on argumentation. Subsequently, some views are explained on the intriguing topics of ‘dissensus’ and ‘deep disagreement’. After a discussion of three different approaches to the treatment of types of argumentation some classical themes from antique argumentation theory are revisited. The new research area of visual argumentation is explored in the next part. The volume concludes with three reports of experimental studies concerning argumentative discourse.